Genetic variation in Aechmea winkleri, a bromeliad from an inland Atlantic rainforest fragment in Southern Brazil. (February 2015) - Goetze, Márcia; Büttow, Miriam Valli; Zanella, Camila Martini; Paggi, Gecele Matos; Bruxel, Manuela; Pinheiro, Felipe Grillo; Sampaio, Jamilla Alves Trindade; Palma-Silva, Clarisse; Cidade, Fernanda Witt; Bered, Fernanda
Abstract: We investigated the genetic diversity and structure of Aechmea winkleri Reitz, an endemic bromeliad found in Southern Brazilian Atlantic rainforest. Seven nuclear microsatellite markers were used to analyze 162 samples from four localities sampled throughout the entire geographic distribution of the species. Results indicate relatively high levels of genetic diversity with an average of allelic richness of 3.57, and observed and expected heterozygosity of 0.559 and 0.608, respectively. The within-inbreeding coefficient was low, ranging from −0.011 to 0.094. All localities significantly deviated from Hardy–Weinberg equilibrium with three of them showing heterozygosites deficiency. Most of the genetic variation (96.64%) was found within localities. No reduction in population size (bottleneck) was detected. Low levels of genetic differentiation among localities were found with pairwise F ST comparisons varying from 0.021 to 0.075. Bayesian analyses revealed that A. winkleri is composed by two genetic groups. The number of migrants per generation was high (>1), which maintain localities' cohesion and gene flow. Despite genetic erosion was not detected in the present study, our results revealed that the four localities sampled actually represent one population, the only known so far in nature. Management strategies for A. winkleri conservation should be undertaken as it is an endemic species which occurs in a biome that has gone through major deforestation and fragmentation. This would avoid the increase of inbreeding rates and the loss of genetic diversity. Highlights: A. winkleri localities present high genetic diversity and low genetic structure. Species life-history traits are contributing to the maintenance of genetic diversity. In a genetic sense only one population of A. winkleri is found in nature. Conservation strategies are needed to protect the endangered A. winkleri .